Self‐Reported Changes in Sun‐Protection Behaviors at Different Latitudes in Australia. (22nd March 2016) - Djaja, Ngadiman; Janda, Monika; Lucas, Robyn M.; Harrison, Simone L.; van der Mei, Ingrid; Ebeling, Peter R.; Neale, Rachel E.; Whiteman, David C.; Nowak, Madeleine; Kimlin, Michael G.
Abstract: Sun exposure is the most important source of vitamin D, but is also a risk factor for skin cancer. This study investigated attitudes toward vitamin D, and changes in sun‐exposure behavior due to concern about adequate vitamin D. Participants ( n = 1002) were recruited from four regions of Australia and completed self‐ and interviewer‐administered surveys. Chi‐square tests were used to assess associations between participants' latitude of residence, vitamin D‐related attitudes and changes in sun‐exposure behaviors during the last summer. Multivariate logistic regression analyses were used to model the association between attitudes and behaviors. Overall, people who worried about their vitamin D status were more likely to have altered sun protection and spent more time in the sun people not concerned about vitamin D. Concern about vitamin D was also more common with increasing latitude. Use of novel item response theory analysis highlighted the potential impact of self‐reported behavior change on skin cancer predisposition due concern to vitamin. This cross‐sectional study shows that the strongest determinants of self‐reported sun‐protection behavior changes due to concerns about vitamin D were attitudes and location, with people at higher latitudes worrying more. Abstract : Exposure to ultraviolet radiation from the sun is the most important source of vitamin D, but is also a risk factor for skin cancer. People who worried about their vitamin D status were more likely to have altered their sun protection behaviors and spent more time in the sun than those not worried about vitamin D. Use of novel item response theory analysis highlighted the potential impact of such behavior change on skin cancer predisposition. The strongest determinants of self‐reported sun protection behavior changes due to vitamin D concerns were attitudes and location, with people at higher latitudes worrying more.